PEDAGOGICAL SYNTHESIS AND EFFECTIVENESS OF INSTRUCTIONAL TECHNOLOGIES IN THE DELIVERY OPEN AND DISTANCE LEARNING PROGRAMME - Ojokheta, K. O (African Journal of Educational Management, 2021)
This paper describes vividly the various forms of instructional technologies as well as the generation of communication technologies available for the delivery of distance education programmes. This is premised on the belief that policy planners and practitioners in distance education need to possess in-depth knowledge of these technologies so as to guide them on the choice of the most appropriate technology to adopt in the delivery of distance education programmes. The paper also discusses the pedagogical effectiveness of each technology in relation to these programmes. This is also premised on the belief that the more familiar tutors are with instructional technologies, the more effective their will be. This was concluded with the criteria that distance education practitioners and managers can adopt or rely upon in the choice of the most appropriate technology in the delivery of distance education programmes with particular reference to Nigeria.